O envelhecer na visão de idosos com seqüelas do acidente vascular encefálico - Bottós, Maria Regina Macedo (2007)
As longevity increases, one can observe a greater occurrence of non-transmissible chronic diseases such as Cerebral Vascular Accidents, which are in first place. This disease can result in death or leave incapacitating sequelae, such as partial or total disability, causing serious personal, family and societal effects. The study s general objective refers to this context, which presents the reality of aging in association with the disease, through an investigation on the personal and social impacts of aging with sequelae from a Cerebral Vascular Accident. The study was carried out with elderly who had suffered a Cerebral Vascular Accident and showed light to moderate levels of hemiplegia. The study s results revealed that, considering the subjective and social-cultural aspects related to the aging process, the impacts resulting from a Cerebral Vascular Accident were mainly characterized by loss of autonomy, and this change can have a positive as well as negative meaning, depending on the family and economic support given to the elderly